PERBANDINGAN PENGGUNAAN BUSI TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR HONDA SCOOPY TAHUN 2016 - Budiyono, Budiyono; Prasetyo, Imam; Perdana, Muhammad Faza (Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
Spark plug is a spare part that is installed on an internal combustion engine with an electrode tip in the combustion chamber. The purpose of this study was to determine how much influence the use of standard spark plugs, iridium spark plugs, platinum spark plugs, and racing spark plugs has on fuel consumption on Honda motorcycles. Scoopy. The method used in this research is the experimental method or direct experiments. Turn on the motorbike, then walk for a distance of 60 Km, with an average speed of 50 to 80 Km which is in accordance with what was determined in the study. By doing the no-load test 2 times in each experiment to be tested. Research results Iridium spark plugs (Denso IU27) in 1 liter of fuel can cover a distance of 50.42 km/l, fuel consumption of platinum spark plugs (CPR6EAGP-9) in 1 liter of fuel can cover a distance of 55.04 km/l, while consumption Busi Racing fuel (TDR 071) in 1 liter can cover a distance of 47.61 Km/L, so this study shows that using Platinum Spark Plugs can reduce fuel consumption.Keywords : Spark Plugs, Fuel Consumptio